Effects Of Human Wharton's Jelly Mesenchymal Stem Cells On In Vitro Functions Of Aged Mouse Clonogenic Cardiac Cells - Ng, Wai Hoe (2019)
Exposure of aged stem cells to young systemic environment has shown to improve their functions in vivo. While heart disease commonly affects elderly patients, it is unclear if biologically young Wharton’s jelly-derived mesenchymal stem cells (MSCs) can improve the functions of aged cardiac c-kit cells (CCs) in vitro. This study examined the effects of MSCs on the functions of aged CCs. CCs were isolated from 1- and 18-month-old C57BL/6N mice and were co-cultured with human MSCs with direct cell-cell contact or separated with a Transwell insert. Stemness, growth kinetics, relative telomere length and telomerase activity of the aged CCs were evaluated in comparison with both young (yCCs) and aged CCs (aCCs) without MSC co-culture. To test the effects of extracellular matrices (ECM) produced from MSCs, CCs were cultured on ECM-derived from MSCs treated with cardiogenic medium. Proliferation and oxidative stress assays were performed to evaluate the effect of MSC-derived ECM on CCs. All data were analysed using ANOVA. The primary aCCs showed significantly lower clonogenicity compared to yCCs (9.5 ± 2.9% vs. 21.2 ± 4.4%; p < 0.05). Following clonogenic expansion, only CD90PosCD140aPosCD166Neg cells were expanded in the aCCs, which were different from the phenotype of yCCs (CD90NegCD140aNegCD166Pos) as assessed by flow cytometry. Clonogenic aCCs showed comparable telomere length to yCCs. However, these cells showed lower Gata4, Nkx2.5 and Sox2 gene expressions, with changes of 2.4, 3767.0, 4.9 folds, respectively. These cells presented a lower sphere formation capability (4 ± 1 vs. 64 ± 19 spheres; p < 0.05) and did not spontaneously differentiate into cardiomyocyte and endothelial lineage. Direct co-culture of both cells increased aCC migration which repopulated 54.6 ± 4.4% of the gap area as compared to aCCs with MSCs in Transwell (42.9 ± 2.6%) and aCCs without MSCs (44.7 ± 2.5%, p < 0.05).